2006
DOI: 10.1017/s0265021505001705
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of patients who require renal replacement therapy after cardiac surgery

Abstract: This study confirms that the in-hospital mortality of patients requiring renal replacement therapy is high and shows a low long-term mortality with reasonable quality of life in patients discharged from hospital alive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Some studies have demonstrated lower health-related quality of life assessed by various instruments in those who experienced and survived AKI than population norms or age-matched and sex-matched controls [40,41]. However, when survivors of AKI were asked about their self-perceived satisfaction with their quality of life, the majority of patients were still satisfied with their state of wellness [41][42][43].…”
Section: Functional Outcomesmentioning
confidence: 99%
“…Some studies have demonstrated lower health-related quality of life assessed by various instruments in those who experienced and survived AKI than population norms or age-matched and sex-matched controls [40,41]. However, when survivors of AKI were asked about their self-perceived satisfaction with their quality of life, the majority of patients were still satisfied with their state of wellness [41][42][43].…”
Section: Functional Outcomesmentioning
confidence: 99%
“…These findings suggest that ''the ends justifies the means'' for costs associated with care of AKI requiring RRT. 26,27,49,50 Based on the 2001 National Hospital Discharge Survey, patients surviving an episode of AKI have an odds ratio of 2 for transfer from the hospital to a short-or long-term care facility. 5 Nearly 30% of all patients surviving to hospital discharge spend a significant amount of time in long-term care facilities.…”
Section: Qolmentioning
confidence: 99%
“…12,52 Over the last few years, several investigators have specifically addressed the longterm outcomes, morbidity and mortality, of this at-risk patient population. 11,12,18,50,[53][54][55] The need for RRT after cardiac surgery occurs in 0.3% to 2.9%, 18,50,53,54 In a retrospective study of cardiac surgery patients with normal preoperative SCr who required RRT for postoperative AKI , only 10% of the original cohort (n ¼ 40) were still alive at 1 year (n ¼ 4). 18 In contrast, a 17% long-term survival (3 years) was described by Landoni et al 50 A retrospective observational study by Hein et al 55 highlights the impact of the need for RRT on long-term survival.…”
Section: Cardiacmentioning
confidence: 99%
“…Patients with AKI not needing dialysis have up to a 4-fold increase in both short- and long-term mortalities, as well as a significantly higher long-term risk of developing end-stage renal disease (ESRD) [2,4,8,9,10,11]. Severe AKI requiring dialysis during the perioperative period carries up to 60% mortality, compared to an overall mortality of 2-8% after cardiac surgery [12,13,14]. …”
Section: Introductionmentioning
confidence: 99%